Faktor-Faktor yang Berhubungan dengan Pemberian Imunisasi Lanjutan Campak Rubella Pada Balita Usia 18 Bulan Sampai 2 Tahun : Faktor-Faktor yang Berhubungan dengan Pemberian Imunisasi Lanjutan Campak Rubella Pada Balita Usia 18 Bulan Sampai 2 Tahun - Desi Fitriani; Metha Fahriani; Tria Nopi Herdiani; Ruri Mayseptya Sari; Dewi Aprilia Ningsih; Septi Yulidar (Ahmar Metastasis Health Journal, 2021)
Introduction:  The low immunization coverage cannot be separated from the factors that influence immunization, namely health behavior. This study aims to determine the factors associated with the provision of advanced rubella measles immunization to toddlers aged 18 months to 2 years. Methods: The design of this study used an analytic survey with a cross sectional approach. The population in this study were all mothers who had babies aged over 2 years and their mothers who came to the Work Area of ​​the Rimbo Kedui Public Health Center, Seluma Regency as many as 280 toddlers in 2019 who were taken by purposive sampling. Data collection, namely primary and secondary data. The analysis technique used univariate and bivariate (Chi square). Results: There were 30 (53.6%) respondents who gave further immunization against rubella measles to children aged 18 months to 2 years. there were 27 (48.2%) respondents with less knowledge, 32 (57.1%) of them work far away in the working area of ​​the Rimbo Kedui Public Health Center, Seluma Regency 50 (89.3%) of respondents had the role of health workers in the Rimbo Kedui Public Health Center Seluma Regency. Conclusion: There is a relationship between knowledge and work with the provision of advanced rubella measles immunization with a close relationship category and there is a relationship between the role of health workers and the provision of advanced rubella measles immunization to children aged 18 months to 2 years. Pendahuluan : Rendahnya cakupan imunisasi tidak lepas dari faktor yang mempengaruhi imunisasi yaitu perilaku kesehatan. Penelitian bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan pemberian imunisasi lanjutan campak rubella pada balita usia 18 bulan sampai 2 tahun. Metode : penelitian ini survey analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki bayi berusia diatas 2 tahun dan ibunya yang datang ke Wilayah Kerja Puskesmas Rimbo Kedui Kabupaten Seluma sebanyak 280 balita pada tahun 2019 yang diambil secara purposive sampling. Pengumpulan data yaitu data primer dan sekunder. Teknik analisis menggunakan Univariat dan bivariat (Chi square). Hasil : Terdapat 30 (53,6%) responden memberikan imunisasi lanjutan campak rubella pada balita usia 18 bulan sampai 2 tahun dan terdapat 27 (48,2%) responden berpengetahuan kurang, 32 (57,1%) responden bekerja yang jauh dan terdapat 50 (89,3%) responden ada peran petugas kesehatan di Wilayah Kerja Puskesmas Rimbo Kedui Kabupaten Seluma. Kesimpilan: Ada hubungan antara pengetahuan dan pekerjaan  dengan pemberian imunisasi lanjutan campak rubella dengan  kategori hubungan erat dan  ada hubungan antara peran petugas kesehatan dengan pemberian imuniasi lanjutan campak rubella pada balita usia 18 bulan sampai 2 tahun.